2013
DOI: 10.1002/elps.201300281
|View full text |Cite
|
Sign up to set email alerts
|

A high‐sensitivity LIF detector with silver mirror coating detection window and small‐angle optical deflection from collinear system for CE

Abstract: An LIF detector was integrated into a CE system based on silver mirror coating detection window and small-angle optical deflection from collinear configuration. For this detection scheme, the incident light beam was focused on capillary through the edge of a lens, resulting in a small deflection angle that deviated 18° from the collinear configuration. Meanwhile, the excitation light and emitted fluorescence were effectively reflected by silver mirror coating at the detection window. The fluorescence was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The method of coating detection window with silver has been depicted in our previous work . Briefly, a detection window was made on the capillary by removing a 0.5 cm section of polyimide coating, which was then rinsed by deionized water and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The method of coating detection window with silver has been depicted in our previous work . Briefly, a detection window was made on the capillary by removing a 0.5 cm section of polyimide coating, which was then rinsed by deionized water and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…By using a colinear optical arrangement proposed 20 years ago , Li et al. have increased the sensitivity of LIF detection of a 16 factor using an Ag mirror around the capillary window and a small 18° deflection angle prior to the normal of the capillary . Ag nanorods (ND) has showed high metal enhanced fluorescence used in microfluidic systems, with a multilayer of SiO 2 Ag‐NDs.…”
Section: Detectionmentioning
confidence: 99%
“…The LOD of FITC was estimated to be 2 pM (S/N = 3). Li et al [26] reported a similar LIF detection system with a small-angle (18°) optical deflection from collinear configuration with silver mirror coating detection window, which greatly enhanced fluorescence intensity. The LOD of 0.5 pM FITC (S/N=3) was obtained.…”
Section: The Nonconfocal Lif Arrangementmentioning
confidence: 99%